Sungai Chiling water quality module - Mohamad Kasim, Mohamad Roslan; Nordin, Siti Fatimah; Sayang Sukasih Parman, Rhyma Purnama (Jabatan Perhutanan Negeri Selangor, 2024)
This article or chapter discuss on the water quality status in term of physical aspects of Sungai Chiling to support the aquatic lives and also its water availability to fulfill the amount of clean water supply required by the relevant consumers.